2022
DOI: 10.7203/leeme.49.24249
|View full text |Cite
|
Sign up to set email alerts
|

Actividades musicales en escuelas infantiles de Hong Kong: Análisis de contenido de los informes de Revisión de Calidad

Abstract: In Hong Kong, the Education Bureau (EDB) assesses the quality of services provided to children in local kindergartens. Quality Review (QR) reports of kindergartens that pass the assessment are published on EDB’s website. We conducted a content analysis of 164 QR reports to examine the alignment between the music activities alluded to and the curriculum objectives established for music in official policies. A coding scheme was developed using both inductive and deductive approaches. High inter-reliability was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Teachers were found to engage children in music and arts activities during approximately 9% of the time, which was significantly less than the time they spent on other areas of learning. Similar trends have been identified in Asian societies such as Singapore (Bautista et al, 2018) and Hong Kong (Ho & Bautista, 2022). Furthermore, scholars have argued that teachers in preschools often use music as a tool to teach children content pertaining to other areas of learning, whereas activities centered on music per se tend to be carried out less often (Lau & Grieshaber, 2018; Samuelsson et al, 2009).…”
Section: Literature Reviewsupporting
confidence: 77%
See 2 more Smart Citations
“…Teachers were found to engage children in music and arts activities during approximately 9% of the time, which was significantly less than the time they spent on other areas of learning. Similar trends have been identified in Asian societies such as Singapore (Bautista et al, 2018) and Hong Kong (Ho & Bautista, 2022). Furthermore, scholars have argued that teachers in preschools often use music as a tool to teach children content pertaining to other areas of learning, whereas activities centered on music per se tend to be carried out less often (Lau & Grieshaber, 2018; Samuelsson et al, 2009).…”
Section: Literature Reviewsupporting
confidence: 77%
“…As a result of globalization, official preschool curriculum frameworks around the world have been largely homogenized in recent decades (Organisation for Economic Co-Operation and Development [OECD], 2019 ). This has clearly been observed in music education, an area in which similarities between curricula across nations and jurisdictions outnumber differences (Campbell & Scott-Kassner, 2019; Essa & Burnham, 2019; Ho & Bautista, 2022). Contemporary curriculum frameworks emphasize the importance of exposing young children to varied and diverse musical activities daily, given the multiple benefits of music education in promoting children’s holistic development and learning (Sullivan, 2016).…”
Section: Literature Reviewmentioning
confidence: 87%
See 1 more Smart Citation
“…A content analysis of 164 QR reports focused on exploring the types of musical activities in kindergartens was conducted [27]. We found that while the most prevalent musical activities were related to children's development of sensory abilities through music experiences (e.g., singing, rhythm, beat, movement, and instrumental music), activities related to musical creativity and self-expression were rarely mentioned in the QR reports.…”
Section: Kindergarten Music Education In Hong Kongmentioning
confidence: 99%
“…Moreover, about half of participants viewed behavior in their classrooms in terms of classroom control and behavioral management, rather than as a reflection of children's self-regulatory skills (Willis et al, 2014). Similarly, ECE teachers around the world use music (primarily action songs) to handle classroom routines and transitions and to engage children in their work (Hamilton, & Murphy, 2023;Ho, & Bautista, 2022), rather than as a means of encouraging children's musical creativity and self-expression. In a study conducted in Bangladesh (Islam, 2021), most kindergarten teachers expressed that children were too young to understand self-regulation, which in their view justified their difficulties to self-regulate themselves.…”
Section: Kindergarten Teachers' Knowledge and Beliefs Of Self-regulationmentioning
confidence: 99%